Geographic Variations in Cardiovascular Disease Mortality Among Asian American Subgroups, 2003–2011. Issue 7 (12th July 2017) - Pu, Jia; Hastings, Katherine G.; Boothroyd, Derek; Jose, Powell O.; Chung, Sukyung; Shah, Janki B.; Cullen, Mark R.; Palaniappan, Latha P.; Rehkopf, David H.
Abstract : Background: There are well‐documented geographical differences in cardiovascular disease (CVD) mortality for non‐Hispanic whites. However, it remains unknown whether similar geographical variation in CVD mortality exists for Asian American subgroups. This study aims to examine geographical differences in CVD mortality among Asian American subgroups living in the United States and whether they are consistent with geographical differences observed among non‐Hispanic whites. Methods and Results: Using US death records from 2003 to 2011 (n=3 897 040 CVD deaths), age‐adjusted CVD mortality rates per 100 000 population and age‐adjusted mortality rate ratios were calculated for the 6 largest Asian American subgroups (Asian Indian, Chinese, Filipino, Japanese, Korean, and Vietnamese) and compared with non‐Hispanic whites. There were consistently lower mortality rates for all Asian American subgroups compared with non‐Hispanic whites across divisions for CVD mortality and ischemic heart disease mortality. However, cerebrovascular disease mortality demonstrated substantial geographical differences by Asian American subgroup. There were a number of regional divisions where certain Asian American subgroups (Filipino and Japanese men, Korean and Vietnamese men and women) possessed no mortality advantage compared with non‐Hispanic whites. The most striking geographical variation was with Filipino men (age‐adjusted mortality rate ratio=1.18; 95% CI, 1.14–1.24) and Japanese men (age‐adjusted mortality rate ratio=1.05; 95% CI: 1.00–1.11) in the Pacific division who had significantly higher cerebrovascular mortality than non‐Hispanic whites. Conclusions: There was substantial geographical variation in Asian American subgroup mortality for cerebrovascular disease when compared with non‐Hispanic whites. It deserves increased attention to prioritize prevention and treatment in the Pacific division where approximately 80% of Filipinos CVD deaths and 90% of Japanese CVD deaths occur in the United States.